Cholinergic tone abnormalities and relationships with smoking severity in human cigarette smokers: exploratory positron emission tomography study using 18FVAT - Moeller, Scott J; Weinstein, Jodi J; Varnas, Benjamin; Orellano, Olivia; Gil, Roberto; Perlman, Greg; Abeykoon, Sameera; Meng, Jiayan; Oprea, Ingrid; Hu, Bao; Qu, Wenchao; Slifstein, Mark; et al. (Molecular psychiatry, 2025)
Nicotine acts on the brain cholinergic system to drive the rewarding effects of cigarettes and perpetuate smoking. Prior studies in human smokers have used positron emission tomography (PET) to characterize differences in postsynaptic nicotinic acetylcholine receptors (nAChRs). However, preclinical studies indicate that nicotine also modulates presynaptic cholinergic targets that have implications for transmission, including the vesicular acetylcholine transporter (VAChT). To date, there is a paucity of studies imaging presynaptic targets in human smokers. We conducted an initial PET neuroimaging study with [18F]VAT, which indexes VAChT availability (presynaptic marker of cholinergic tone), in 12 healthy smokers and 13 demographically-matched healthy non-smokers. We tested for group differences in VAChT availability, measured as total distribution volume (VT), in the striatum (main region of interest) and in multiple cortical and subcortical extrastriatal regions. Within smokers, we also tested correlations between VAChT availability and indices of smoking chronicity and tobacco self-administration. Smokers had higher [18F]VAT VT than non-smokers in multiple cortical and subcortical regions (p < 0.05uncorrected). There were no group differences in the striatum. Within smokers, VT in the dorsolateral prefrontal and temporal cortices was positively correlated with smoking chronicity (p < 0.05corrected). This study provides first-line evidence of presynaptic cholinergic differences between smokers and non-smokers, such that VAChT is upregulated in smokers and associated with chronicity. Future studies with larger samples are needed to verify these initial effects. With confirmation, these findings could inform the development of new VAChT-targeting therapeutics that could potentially benefit smokers who have been unable to quit with currently available treatments.Nicotine acts on the brain cholinergic system to drive the rewarding effects of cigarettes and perpetuate smoking. Prior studies in human smokers have used positron emission tomography (PET) to characterize differences in postsynaptic nicotinic acetylcholine receptors (nAChRs). However, preclinical studies indicate that nicotine also modulates presynaptic cholinergic targets that have implications for transmission, including the vesicular acetylcholine transporter (VAChT). To date, there is a paucity of studies imaging presynaptic targets in human smokers. We conducted an initial PET neuroimaging study with [18F]VAT, which indexes VAChT availability (presynaptic marker of cholinergic tone), in 12 healthy smokers and 13 demographically-matched healthy non-smokers. We tested for group differences in VAChT availability, measured as total distribution volume (VT), in the striatum (main region of interest) and in multiple cortical and subcortical extrastriatal regions. Within smokers, we also tested correlations between VAChT availability and indices of smoking chronicity and tobacco self-administration. Smokers had higher [18F]VAT VT than non-smokers in multiple cortical and subcortical regions (p < 0.05uncorrected). There were no group differences in the striatum. Within smokers, VT in the dorsolateral prefrontal and temporal cortices was positively correlated with smoking chronicity (p < 0.05corrected). This study provides first-line evidence of presynaptic cholinergic differences between smokers and non-smokers, such that VAChT is upregulated in smokers and associated with chronicity. Future studies with larger samples are needed to verify these initial effects. With confirmation, these findings could inform the development of new VAChT-targeting therapeutics that could potentially benefit smokers who have been unable to quit with currently available treatments.